Occurrence and Distribution of Synthetic Organic Substances in Boreal Coniferous Forest Soils Fertilized with Hygienized Municipal Sewage Sludge - Mats Tysklind; Kenneth Sahlén; Richard Lindberg (MDPI AG, 2013)
The occurrence and distribution of synthetic organic substances following application of dried and granulated (hygienized) municipal sewage sludge in Swedish boreal coniferous forests were investigated. Elevated concentrations of triclosan (TCS), polybrominated diphenyl ethers (PBDEs), and polychlorinated biphenyls (PCBs) were detected in the humus layer. Concentrations of ethinyl estradiol (EE2), norfloxacin, ciprofloxacin, ofloxacin (FQs), and polyaromatic hydrocarbons (PAHs) were not significantly influenced. Maximum concentrations in humus were as follows (in ng/g dry matter): TCS; 778; PBDEs; 25; and PCB7; 16.7. Fertilization did not alter the levels of the substances in mineral soil, ground water, and various types of samples related to air. Further research within this area is needed, including ecotoxicological effects and fate, in order to improve the knowledge regarding the use of sludge as a fertilizing agent. Continuous annual monitoring, with respect to sampling and analysis, should be conducted on the already-fertilized fields.